The conscience of the basque society - Gurrutxaga Abad, Ander; Unceta, Alfonso (Papers. Revista de Sociologia, 2007)
The article defends the hypothesis that the conscience of the basque society dependsfor its affirmation on the institutions and the mechanisms that work in the process of institutionalization of the immediate life. The conscience of the community it is not the product of what separates people but of which it unites them in a plural society. This union is between the processes that compose the immediate life and the expectations that are created through it.